Development of Virtual Simulations for Medical Team Training: An Evaluation of Key Features. Issue 1 (June 2018) - Howe, Jessica; Puthumana, Joseph; Hoffman, Daniel; Kowalski, Rebecca; Weldon, Danielle; Miller, Kristen; Weyhrauch, Peter; Niehaus, James; Bauchwitz, Benjamin; McDermott, Ashley; Ratwani, Raj
Medical team training (MTT) conducted in a virtual environment fosters growth in cognitive, technical, and clinical aptitudes while offering advantages of flexibility, cost, and ease of scheduling over traditional high-fidelity simulations. Growing technology facilitates innovations to improve the ability to emulate roles, rules, resources, and fidelity. Our objective was to evaluate elements of key features that inform technical specifications for virtual simulations. A narrative review included 27 articles as relevant to elaborate on five key features identified as critical to development of virtual environments for MTT: automated assessment, task fidelity, interface modality, virtual teammates, and adaptability. Designers continue to improve the technology of virtual reality to create better and more enhanced training modules. We must better understand how variances in simulation features impacts performance outcomes and learned behavior. Future research can more deeply examine features beyond the five reviewed here to guide development of effective, cost-efficient virtual simulations for MTT.